Descartes and the body-machine - Aguilar, Maria Teresa (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This text describes the scientific medical atmosphere of Holland during century XVII, context in which the Cartesian model of body-machine is elaborated, and the intellectual relation that Descartes maintained with doctors and university professors (Harvey, among others). On the other hand, the text puts in evidence the traditional dualism attributed to Descartes, according to a detailed reading of his texts, in that the thesis of strict dualism is released by trialistic interpretations of authors like Monroy-Nasr.
Keywords: relationship mind-body; trialism; dualism; pineal gland; body-machine